Converting plastic-contaminated agricultural residues into fit-for-purpose biochar soil amendment: an initial study - Qiuyu Yu; Xuhui Zhang; Tao Gao; Xueliu Gong; Jiarong Wu; Shuai Tian; Biao Ma; Lujiang Xu; Stephen Joseph; Jufeng Zheng; Rongjun Bian; Lianqing Li (Biochar)
Abstract Addressing agricultural plastic pollution is vital for ecosystem sustainability. Shifting from traditional waste treatments to a sustainable pathway presents both challenges and opportunities for global plastic management. This study investigated the properties and environmental applications of biochar derived from honeydew melon vines contaminated with plastic hanging ropes, pyrolyzed at temperatures of 300, 500, and 700 °C. The resulting biochars were evaluated for their ability to remove Pb and Cd from aqueous solutions. Additionally, a Chinese cabbage pot experiment was conducted to assess the impact of biochar on Pb and Cd immobilization and plant growth in contaminated soil. Results revealed that the properties of biochar varied with pyrolysis temperature. Specifically, incomplete carbonization of plastic ropes was observed at 300 °C, while biochar produced at 500 °C (BC500) showed a higher yield and contained higher levels of available P and K compared to the biochar produced at 700 °C (BC700). The presence of polycyclic aromatic hydrocarbons (PAHs) in biochars increased with temperature but remained within recommended limits. BC500 exhibited the highest adsorption capacities for Pb and Cd at 127 mg g−1 and 36 mg g−1, respectively. Soil amendment with BC500 and BC700 significantly improved soil pH, increased the availability of nutrients and microbial biomass, and effectively immobilized Pb and Cd in the soil. Consequently, the biomass yield of Chinese cabbage was enhanced by 119 % and 86 % under BC500 and BC700, respectively. Moreover, the Pb and Cd content in cabbage decreased by more than 80 % and 29 %, respectively. However, PAHs levels in cabbage leaves increased from 9.2 ng g−1 in the control to 20.8 ng g−1 and 30.4 ng g−1 under BC500 and BC700, respectively, remaining below China’s standard for benzo(a)pyrene. This study suggests pyrolyzing plastic-contaminated crop residues at 500 °C is a feasible strategy for waste recycling. Graphical Abstract